Analysis of the Success of Implementing the Srikandi Application on the Efficiency of Public Service Administration Through the Delone and Mclean Information System Model at the Regional Secretariat of Solok City, West Sumatra Province - Yulia Wulan Dhari; Ana Frahesti; Fitri Suherini; Rino Esa Maha Putra; Yohannes Simamora; Jhon Veri (Jurnal Multidisiplin Sahombu, 2026)
The implementation of the Integrated Dynamic Archiving Information System (SRIKANDI) application in government agencies aims to improve the efficiency of public service administration through integrated digital archive management. However, in its implementation, problems related to system quality, information quality, and service quality are still encountered, which have the potential to affect administrative efficiency and user satisfaction. This study aims to analyze the success of the SRIKANDI application implementation on the efficiency of public service administration through the DeLone and McLean Information System Success Model at the Regional Secretariat of Solok City, West Sumatra Province. This study uses a quantitative approach with a survey method. The population and sample of the study were all employees who use the SRIKANDI application, with a sampling technique using saturated sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS. The results show that system quality, information quality, and service quality influence the efficiency of public service administration and user satisfaction. In addition, the efficiency of public service administration also influences user satisfaction. Therefore, it can be concluded that the success of the SRIKANDI application implementation is influenced by the quality of the information system that supports increased efficiency and user satisfaction.